The Strategic Role of Fatwa DSN-MUI in the Development of Islamic Banking in Indonesia: An Analysis of Banking Regulations and Products Based on the Provisions of Islamic Law - Zikra, Alfiandi; Nasution, Muhammad Syukri Albani; Siregar, Ramadhan Syahmedi (JURNAL AKTA, 2024)
This journal discusses the role of the Indonesian Ulema Council (MUI) and the birth of Bank Muamalat Indonesia (BMI) as the first step in the establishment of Islamic banks in Indonesia. Bank Muamalat became a pioneer, followed by other Islamic banks. The focus is on the DSN-MUI fatwa which has a strategic role in shaping Islamic banking regulations and products, especially related to the collection and distribution of funds. This research uses descriptive qualitative methods with secondary data from related journals and books. The DSN-MUI fatwa is an important guideline for Islamic financial institutions in Indonesia. The analysis reveals that DSN-MUI plays a central role in dealing with the problems of Islamic banking practices. The research presents the background of the birth of DSN-MUI, the method of fatwa determination, and various fatwa products covering banking products, capital markets, Islamic insurance, export/import, and others. There are 116 fatwas that help form the legal basis of Islamic banking in Indonesia. This study underlines the importance of synchronization between fatwa as theory and practice in the field, especially in the collection and distribution of Islamic banking funds.